A Comparative Analysis of Reciprocal Peer Learning and Traditional Teaching Approaches on Learners’ Retentive Ability in Literary Appreciation - Augusta Chiedu Assimonye; Ugochukwu Poly Ngozi Amadi (Journal Majelis Paspama, 2023)
The study examined the comparative effects of Reciprocal Peer Learning (RPL) and Traditional Teaching Approaches (TTA) on learners’ retentive ability in literary appreciation among senior secondary school students in Anambra State, Nigeria. The study employed a quasi-experimental pretest-posttest non-equivalent control group design involving 65 SSII students. The experimental group was taught literary appreciation using Reciprocal Peer Tutoring (RPT), while the control group used the conventional method. The Literature-in-English Achievement and Retention Test (LART) served as the instrument, validated and found reliable (r = 0.721). Data were analyzed using mean, standard deviation, and ANCOVA at a 0.05 significance level to determine differences in students’ achievement and retention in literary appreciation. The results showed that students taught literary appreciation using Reciprocal Peer Tutoring (RPT) achieved higher retention than those taught with the conventional method. The RPT group had a posttest mean of 68.83 (SD = 10.02) and a retention mean of 72.68 (SD = 10.72), while the conventional group had a posttest mean of 35.61 (SD = 9.72) and a retention mean of 36.98 (SD = 9.61). The retention mean gain of 3.85 for RPT exceeded 1.37 for the conventional method. ANCOVA results (F = 183.169, p = .000) indicated a significant difference favoring RPT. The result indicated that peer collaboration and active engagement promoted deeper comprehension and better memory retention of literary concepts. The study concluded that Reciprocal Peer Learning enhances learners’ retentive ability and should be integrated into Literature-in-English instruction to improve learning outcomes.